2019
DOI: 10.1016/j.schres.2018.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the MUSIC Model of Motivation Inventory for use with cognitive training for schizophrenia spectrum disorders: A multinational study

Abstract: wrote part of the first draft of the manuscript, contributed to study design, adapted the MUSIC Model Inventory, recruited participating sites, organized data and conducted descriptive analyses. Brett D. Jones adapted the MUSIC Model Inventory, conducted statistical analyses, checked back translations of the Inventory for accuracy, and wrote part of the first draft of the manuscript. Alice M. Medalia conceived of the study, adapted the MUSIC Model Inventory, and contributed to the developing manuscript. Author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…It is important to provide evidence that the five MUSIC perceptions are distinct in educational settings; otherwise, it is possible that some of the MUSIC perceptions may be very similar to one another and measure the same constructs. Results from several studies have confirmed that students' MUSIC perceptions are distinct in a variety of educational settings, including courses in professional schools (Jones, Byrnes, & Jones, 2019;Pace, Ham, Poole, & Wahaib, 2016), undergraduate courses (Chittum, Jones, & Carter, 2019;Jones & Wilkins, 2013), middle and high school classes (Chittum & Jones, 2017;Parkes, Jones, & Wilkins, 2017), elementary school classes (Jones & Sigmon, 2016), and clinical training settings (Hansen et al, 2019). Furthermore, these studies have been conducted in a variety of cultures and countries, including Canada, Denmark, and Japan (Hansen et al, 2019); China and Columbia (Jones, Li, & Cruz, 2017); Egypt (Mohamed, Soliman, & Jones, 2013); and Iceland (Schram & Jones, 2016).…”
Section: Evidence For the Music Modelmentioning
confidence: 91%
“…It is important to provide evidence that the five MUSIC perceptions are distinct in educational settings; otherwise, it is possible that some of the MUSIC perceptions may be very similar to one another and measure the same constructs. Results from several studies have confirmed that students' MUSIC perceptions are distinct in a variety of educational settings, including courses in professional schools (Jones, Byrnes, & Jones, 2019;Pace, Ham, Poole, & Wahaib, 2016), undergraduate courses (Chittum, Jones, & Carter, 2019;Jones & Wilkins, 2013), middle and high school classes (Chittum & Jones, 2017;Parkes, Jones, & Wilkins, 2017), elementary school classes (Jones & Sigmon, 2016), and clinical training settings (Hansen et al, 2019). Furthermore, these studies have been conducted in a variety of cultures and countries, including Canada, Denmark, and Japan (Hansen et al, 2019); China and Columbia (Jones, Li, & Cruz, 2017); Egypt (Mohamed, Soliman, & Jones, 2013); and Iceland (Schram & Jones, 2016).…”
Section: Evidence For the Music Modelmentioning
confidence: 91%
“…This study employed the MUSIC model of academic motivation [6], which has been employed in both undergraduate and graduate/medical student groups as an assessment of student motivation to learn [6,7,[11][12][13][14]. We found that the Usefulness of the course to their future and the ability to Succeed in the course were the highest indicators for academic motivation in both the spring and fall semesters.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers often use the MUSIC Inventory (Jones, 2012/2020) to assess students’ MUSIC perceptions because it provides scales with similar response options for each MUSIC model component and has been shown to produce valid scores in a variety of educational environments, including elementary school (Jones & Sigmon, 2016), middle and high school (Chittum & Jones, 2017; Parkes et al, 2017), college (Jones & Carter, 2019; Jones & Skaggs, 2016; Tendhar et al, 2017; Wilkins et al, 2021), professional schools (Gladman et al, 2020; Jones et al, 2019; Pace et al, 2016), and psychological clinics (Hansen et al, 2019; Saperstein et al, 2020). The MUSIC Inventory has been translated into many different languages, and researchers have documented that it produces valid scores when translated to Arabic (Mohamed et al, 2013), Chinese (Jones et al, 2017), Danish (Hansen et al, 2019), Icelandic (Schram & Jones, 2016), Japanese (Hansen et al, 2019), and Spanish (Author et al, 2017). These studies have also provided factor analytic evidence that the five MUSIC components are distinct.…”
Section: Literature Reviewmentioning
confidence: 99%